2009
DOI: 10.1111/j.1439-0272.2008.00906.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between semen quality and seminal plasma components: alpha-glucosidase, fructose and citrate in infertile men compared with a normospermic population of Tunisian men

Abstract: The aim of this study was to evaluate the correlation between the secretory function of the male accessory glands and sperm parameters in normospermic controls and infertile patients. One hundred and fifty-nine men were investigated: they were composed of two groups: normospermic (n = 37) and infertile (n = 122) men with altered sperm characteristics. These infertile men were divided into the following groups: asthenozoospermia (n = 38), teratozoospermia (n = 40) and asthenoteratozoospermia (n = 44). The patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 43 publications
3
24
0
1
Order By: Relevance
“…We found a significant increase in α‐glucosidase concentration after 6 months of therapy, which aligns with the higher levels of α‐glucosidase observed in fertile compared to infertile men by Zopfgen et al (), and the positive correlation between α‐glucosidase activity and motility by Roaiah et al (). Some studies did not observe a difference in α‐glucosidase activity relative to spermatozoa motility (Krause & Bohring, ; Lenzi et al, ; Said et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…We found a significant increase in α‐glucosidase concentration after 6 months of therapy, which aligns with the higher levels of α‐glucosidase observed in fertile compared to infertile men by Zopfgen et al (), and the positive correlation between α‐glucosidase activity and motility by Roaiah et al (). Some studies did not observe a difference in α‐glucosidase activity relative to spermatozoa motility (Krause & Bohring, ; Lenzi et al, ; Said et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Non‐viscous and viscous specimens exposed to chymotrypsin have shown little if any change in total motility, forward progression motility, concentration, pH, or volume, but do exhibit a slight change in sperm motility patterns (Chen, Lu, Xu, Huang, & Lu, ). Increased levels of α‐glucosidase activity, a biomarker that is positively correlated with semen quality (Said, Galeraud‐Denis, Carreau, & Saad, ; Zöpfgen et al, ), are also observed following liquefaction with chymotrypsin (Xu et al, ), further supporting the minimal impact of chymotrypsin on semen quality. Bromelain, a thiol proteolytic enzyme found in the stem of pineapples, has also been used to treat viscous seminal plasma from dromedary camels, and did not affect sperm motility (Monaco et al, ).…”
Section: Introductionmentioning
confidence: 91%
“…NAG and fructose, originated in male accessory glands, are released in seminal plasma by genital tract (Said et al ., ). So, NAG and fructose levels are easy to be detected in seminal plasma if genital duct is not completely obstructed.…”
Section: Discussionmentioning
confidence: 97%
“…So, NAG and fructose levels are easy to be detected in seminal plasma if genital duct is not completely obstructed. Nowadays, alpha‐glucosidase determination is regarded as a noninvasive method in identifying obstructive azoospermia (Viljoen et al ., ; Ojengbede et al ., ; Said et al ., ). Meanwhile, fructose has been reported to be correlated with azoospermia (Buckett & Lewis‐Jones, ).…”
Section: Discussionmentioning
confidence: 97%